Ultrahigh-specific-capacity lithium ion battery based on silicon-oxygen-carbon material and preparation method of ultrahigh-specific-capacity lithium ion battery

A silicon-oxygen-carbon composite material addresses the low capacity and stability issues of silicon-carbon electrodes, achieving high specific capacity and efficient cycle performance for lithium-ion batteries, suitable for energy storage.

CN119133378APending Publication Date: 2024-12-13HANGZHOU GELANFENG NANO SCI&TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410998547.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-24
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Existing lithium-ion batteries face limitations due to low specific capacity and cycle stability of silicon-carbon negative electrode materials, hindering their performance and scalability.

Method used

A lithium-ion battery using a silicon-oxygen-carbon composite material with a specific structural distribution, prepared via chemical vapor deposition, combining silicon, oxygen, and graphene, which enhances lithium ion embedding and structural stability.

Benefits of technology

The battery achieves a discharge specific capacity of 4227.4 mAh/g and 71.80% efficiency, breaking theoretical limits and demonstrating excellent cycle performance, suitable for mass production and energy storage applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119133378A_ABST
    Figure CN119133378A_ABST
Patent Text Reader

Abstract

The invention discloses an ultrahigh specific capacity lithium ion battery based on a silicon-oxygen-carbon material and a preparation method of the ultrahigh specific capacity lithium ion battery, the lithium battery adopts the silicon-oxygen-carbon material as a negative electrode material, and the silicon-oxygen-carbon material is prepared by utilizing a gaseous or liquid silicon source, a gas carbon source and a gas oxygen source. According to the lithium battery based on the silicon-oxygen-carbon material, the first discharge specific capacity can reach 4227.4 mAh / g at the rate of 0.1 C (37.2 mA / g), the theoretical specific capacity limit of a silicon material is broken through, the first efficiency can reach 71.80%, and the lithium battery has good cycle performance. Meanwhile, the silicon-oxygen-carbon material disclosed by the invention can realize mass production, so that the silicon-oxygen-carbon material disclosed by the invention shows huge potential in the field of lithium batteries and is expected to play an important role in a future energy storage technology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a lithium ion battery, and in particular to an ultra-high specific capacity lithium ion battery based on silicon oxygen carbon material and a preparation method thereof. Background Art

[0002] As a core component of modern portable electronic devices, electric vehicles and energy storage systems, the performance of lithium batteries is crucial to the development of these technologies. The performance of lithium batteries depends largely on their negative electrode materials. At present, commercial lithium batteries mainly use graphite as the negative electrode material. However, the theoretical specific capacity of graphite negative electrode is 372mAh / g, which is close to its limit, which has formed a bottleneck for application scenarios that pursue higher energy density. The theoretical specific capacity of silicon material is as high as 4200mAh / g, which is more than ten times that of graphite, and can significantly improve the energy density of lithium batteries. However, the actual measured specific capacity of all materials currently does not exceed 3800mAh / g, which has created a bottleneck for the development of lithium battery negative electrodes. As a new generation of lithium battery negative electrode materials, silicon-carbon materials have attracted much attention due to their high theoretical specific capacity and good electrochemical properties, but the actual capacity of all silicon-carbon material negative electrodes is mostly less than 3000mAh / g.

[0003] Based on this, the present invention proposes a lithium battery based on silicon oxygen carbon negative electrode material. The lithium battery based on silicon oxygen carbon material involved in the present invention has a first discharge specific capacity of 4227.4 mAh / g at a rate of 0.1C (37.2 mA / g), breaking through the theoretical specific capacity limit of silicon materials, and the first efficiency can reach 71.80%, with good cycle performance. At the same time, this material has been able to achieve mass production, which makes the present invention show great potential in the field of lithium batteries and is expected to play an important role in future energy storage technology. Summary of the invention

[0004] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art and provide a lithium ion battery based on silicon oxygen carbon material with high specific capacity and capable of mass production and a preparation method thereof.

[0005] The technical solution adopted by the present invention is as follows:

[0006] A lithium-ion battery with ultra-high specific capacity based on silicon-oxygen-carbon material, using silicon-oxygen-carbon material as negative electrode material, wherein the silicon-oxygen-carbon material is a composite material prepared by in-situ growth using a gaseous or liquid silicon source, a gaseous carbon source, and a gaseous oxygen source, and the composite material has a structural regional distribution feature, which is silicon, silicon-oxygen-carbon, and graphene from the inside to the outside, wherein the graphene is curled graphene.

[0007] The silicon source is liquid organic silicon such as silane or cyclotetramethyldimethylsilane, 3-aminopropyltrimethoxysilane, tri-n-butylaminomethylsilane, etc.

[0008] The carbon source is preferably one or more of methane, ethane, ethylene, acetylene, methanol and ethanol.

[0009] The oxygen source is oxygen, carbon dioxide and other gases.

[0010] The preparation method thereof comprises the following steps:

[0011] By adopting the chemical vapor deposition CVD method, a gaseous or liquid silicon source and a gaseous oxygen source are introduced into a vacuum reaction furnace tube, and a protective atmosphere is introduced, and the temperature is controlled to rise to a specific temperature. After a certain reaction time, a gaseous carbon source and hydrogen are further introduced, carbonized for a certain time, and cooled to room temperature to obtain a silicon-oxygen-carbon material. In particular, a trace amount (usually less than 10 sccm) of oxygen can be introduced simultaneously during the process of introducing the gaseous carbon source and hydrogen for carbonization, which is more conducive to obtaining the silicon-oxygen-carbon material with excellent performance.

[0012] Furthermore, the vacuuming is to vacuumize the reaction furnace tube to 10 -5 ~5×10 3 Pa.

[0013] Furthermore, the molar ratio of the carbon source to hydrogen is 100:1-1:100.

[0014] Furthermore, the protective atmosphere is one or more of argon, nitrogen and helium.

[0015] Furthermore, the specific temperature is 500°C to 2800°C.

[0016] Furthermore, the reaction time is 10-24 hours.

[0017] Furthermore, the carbonization time is 10-14 hours.

[0018] The beneficial effects of the present invention are:

[0019] The present invention selects a specific silicon source and a carbon source to compound silicon and carbon materials, and utilizes the electrical conductivity and structural stability of the carbon materials to effectively alleviate the volume expansion of the silicon material during the cycle. In particular, the prepared silicon oxygen carbon material is two-dimensional. Due to its unique layered structure and large specific surface area, and the obvious structural regional distribution characteristics of the entire material, it can provide more lithium ion embedding sites and a good electrolyte contact interface, effectively improving the specific capacity of the lithium battery. The lithium ion battery prepared by the present invention has an extremely high discharge specific capacity, breaks through the theoretical specific capacity limit of silicon materials, and has excellent cycle performance. In addition, the method of the present invention is simple and can be mass-produced on a large scale, which is conducive to promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is an optical picture of the negative electrode material of Example 1;

[0021] Figure 2 is the Raman spectrum of the silicon oxygen carbon material of Example 1;

[0022] Figure 3 This is a low-resolution TEM image of the silicon-oxygen-carbon material of Example 1;

[0023] Figure 4 This is a high-resolution TEM image of the silicon-oxygen-carbon material of Example 1;

[0024] Figure 5 This is a high-resolution TEM image of the silicon-oxygen-carbon material of Example 1;

[0025] Figure 6 This is the energy spectrum of the silicon-oxygen-carbon material of Example 1. The main elements of the product synthesized by the reaction are silicon, oxygen and carbon;

[0026] Figure 7 This is an optical picture of the lithium battery of Example 1;

[0027] Figure 8 The charge and discharge curve of the lithium battery in Example 1;

[0028] Fig. 9 This is a high-resolution TEM image of the silicon-oxygen-carbon material of Example 2;

[0029] Fig.10 This is a high-resolution TEM image of the silicon-oxygen-carbon material of Example 2;

[0030] Fig.11 This is a high-resolution TEM image of the silicon-oxygen-carbon material of Example 2;

[0031] Fig.12 This is a high-resolution TEM image of the silicon-oxygen-carbon material of Example 2;

[0032] Fig.13 This is the charge and discharge curve of the lithium battery in Example 2. DETAILED DESCRIPTION

[0033] The technical solution of the present invention is further described in detail below in conjunction with the accompanying drawings and specific implementation methods.

[0034] Example 1

[0035] A lithium-ion battery based on silicon-oxygen-carbon material, wherein the preparation method of the silicon-oxygen-carbon material is as follows:

[0036] 1) Preparation of silicon-oxygen-carbon materials

[0037] First, the reaction furnace tube was evacuated to a vacuum degree of 10 -3Pa, then argon, 300sccm silane and 100sccm oxygen were introduced, and the pressure was maintained at 100pa; then the temperature was raised to 800℃ at a rate of 1℃ / min and reacted for 10h under argon protection atmosphere; then the temperature was raised to 1000℃, 200sccm methane and 50sccm hydrogen were introduced, and less than 10sccm oxygen was introduced for reaction, and the reaction was carried out for 24h, and then cooled to room temperature. The optical picture of the obtained product is as follows Figure 1 The Raman spectrum of the product is shown in Figure 2 As shown, at 1580cm -1 The Raman peaks nearby reflect the characteristic peaks of graphene. -1 The peak is the peak of silicon, at 1350cm -1 The nearby peak is caused by oxygen defects in graphene, at 960 cm -1 The Raman peaks nearby are caused by Si-O bonds, which are sufficient to prove that the product is composed of silicon-oxygen-carbon atoms. The morphology of the product under a high-resolution electron microscope is shown in the attached figure. Figure 3 As shown, it shows that a sheet-like silicon oxygen carbon material is formed. The high-resolution TEM of the obtained material is as follows Figure 4 As shown, the silicon oxygen carbon material has good crystallization properties, obvious atomic textures, and the surface is covered with curled graphene material. Lithium ions enter silicon and silicon oxygen carbon through the defects of graphene, thereby achieving sufficient lithium ion infiltration and obtaining a large specific capacity lithium battery. Figure 4 and Figure 5 The high-resolution TEM image shows that the silicon-oxygen-carbon material has obvious structural regional distribution characteristics, which are silicon, silicon-oxygen-carbon, and graphene from the inside to the outside. This feature is stably maintained under a large number of repetitive tests, making the lithium battery of the present invention highly robust. Figure 6 The EDS test again showed that the obtained sample contained silicon, oxygen and carbon materials, indicating that the material composition of this structure is composed of silicon, oxygen and carbon.

[0038] 2) Battery construction process

[0039] First, clean and dry the pad, copper foil and scraper with anhydrous ethanol, and fix the copper foil cut into 8cm wide on the pad with the matte side of the copper foil facing up. Then prepare the slurry, weigh 80wt% active material (i.e., the product of 1) in Example 1), 15wt% Ketjenblack carbon, 5wt% PVDF, dry grind for 30 minutes, add 800μL binder and continue wet grinding for 20 minutes. After the slurry is evenly coated on the matte surface of the copper foil, it is placed in a vacuum drying oven at 80℃ and dried for 12 hours. After drying, the copper foil is cut into discs with a diameter of 12mm with a puncher, and the weight is recorded. Then assemble the battery in the glove box, load the negative electrode shell with rubber ring, shrapnel, gasket, lithium sheet, and diaphragm with a diameter of 16mm from bottom to top, drip 200μL electrolyte to make the diaphragm completely wet, then cover the sample pole piece and positive electrode shell and seal with a hydraulic press, and number them after ensuring that the seal is intact. The battery was placed with the positive electrode facing downward in a common oven at 40°C for 12 hours. Finally, the aged samples were subjected to constant current charge and discharge tests to characterize their specific capacity, cycle performance, and rate performance. Figure 7 shown.

[0040] After testing, the specific capacity and charge-discharge efficiency of the present invention are shown in Table 1, and the charge-discharge curve is shown in Table 1. Figure 8 As shown in the table, the discharge capacity of the lithium-ion battery based on the silicon-oxygen-carbon negative electrode material of the present invention reaches 4227.44 mAh / g in the first cycle at a rate of 0.1C (37.2 mA / g), breaking through the theoretical capacity limit of silicon materials and showing great potential in the field of energy storage. Figure 8 As shown in Table 1, the first charge and discharge efficiency can reach 71.80%, which has good cycle performance.

[0041] Table 1 Cycle performance of the lithium battery of Example 1

[0042]

[0043]

[0044] Example 2

[0045] 1) Preparation of silicon-oxygen-carbon materials

[0046] First, the reaction furnace tube was evacuated to a vacuum degree of 10 -3Pa, then argon, 300 sccm silane and 10 sccm oxygen were introduced, and the pressure was maintained at 100 Pa; then the temperature was raised to 800°C at a rate of 1°C / min and reacted for 15 hours in an argon atmosphere; then the temperature was raised to 1000°C, 300 sccm methane and 100 sccm hydrogen were introduced to react, and 5 sccm oxygen was introduced at the same time, and the reaction was carried out for 10 hours; after the reaction, it was cooled to room temperature; the morphology of the obtained product under a high-resolution electron microscope is shown in the attached figure Fig. 9 As shown, it shows that a sheet-like silicon oxygen carbon material is formed. The high-resolution TEM of the obtained material is as follows Fig.10 , 11 As shown in Figure 12, the silicon oxygen carbon material has good crystallization properties, obvious atomic textures, and the surface is covered with curled graphene material.

[0047] 2) Battery construction process

[0048] First, clean and dry the pad, copper foil and scraper with anhydrous ethanol, and fix the copper foil cut into 10 cm wide on the pad with the matte side of the copper foil facing up. Then prepare the slurry, weigh 85wt% active material (i.e., the product of 1) in Example 2), 7.5wt% Ketjenblack carbon, 7.5wt% PVDF, dry grind for 40 minutes, add 1000μL binder and continue wet grinding for 30 minutes. After the slurry is evenly coated on the matte surface of the copper foil, it is placed in a vacuum drying oven at 85℃ and dried for 18 hours. After drying, the copper foil is cut into discs with a diameter of 12mm with a puncher, and the weight is recorded. Then assemble the battery in the glove box, load the negative electrode shell with rubber ring, shrapnel, gasket, lithium sheet, and diaphragm with a diameter of 16mm from bottom to top, drip 180μL electrolyte to make the diaphragm completely wet, then cover the sample pole piece and positive electrode shell and seal with a hydraulic press, and ensure that the seal is intact and number it. The battery was placed with the positive electrode facing downward in a common oven at 40°C for 18 hours. Finally, the aged samples were subjected to constant current charge and discharge tests to characterize their specific capacity, cycle performance, and rate performance.

[0049] After testing, the specific capacity and charge-discharge efficiency of the present invention are shown in Table 2, and the charge-discharge curve is shown in Table 2. Fig.13 As shown in the table, the discharge capacity of the lithium-ion battery based on the silicon-carbon negative electrode material of the present invention reaches 4131.75 mAh / g in the first cycle at a rate of 0.1C (37.2 mA / g). Considering that the specific capacity of the effective material is 4,860.88 mAh / g, the present invention shows great potential in the field of energy storage. Fig.13 As shown in Table 2, the first charge and discharge efficiency can reach 70.28%, which has good cycle performance.

[0050] Table 2 Cycle performance of lithium battery of Example 2

[0051]

Claims

1. A lithium-ion battery with ultra-high specific capacity based on silicon-oxygen-carbon materials, characterized in that: A silicon-oxygen-carbon material is used as the negative electrode material. The silicon-oxygen-carbon material is a composite material prepared by in-situ growth using a gaseous or liquid silicon source, a gaseous carbon source and a gaseous oxygen source. The composite material has a structural regional distribution characteristic, which is silicon, silicon-oxygen-carbon and graphene from the inside to the outside.

2. The ultra-high specific capacity lithium-ion battery based on silicon oxygen carbon material according to claim 1, characterized in that: The battery has a first discharge specific capacity of 4227.4 mAh / g at a rate of 0.1C (37.2 mA / g), breaking through the theoretical specific capacity limit of silicon materials, and a first efficiency of 71.80%.

3. The ultra-high specific capacity lithium-ion battery based on silicon oxygen carbon material according to claim 1, characterized in that: The silicon source is a gaseous silicon source or a liquid organic silicon, preferably one or more of silane, cyclotetramethyldimethylsilane, 3-aminopropyltrimethoxysilane, and tri-n-butylaminomethylsilane.

4. The ultra-high specific capacity lithium-ion battery based on silicon oxygen carbon material according to claim 1, characterized in that: The carbon source is one or more of methane, ethane, ethylene, acetylene, methanol and ethanol.

5. The ultra-high specific capacity lithium-ion battery based on silicon oxygen carbon material according to claim 1, characterized in that: The silicon oxygen carbon material is prepared by a two-step method, and the preparation method thereof comprises the following steps: By using the chemical vapor deposition (CVD) method, a gaseous or liquid silicon source and a gaseous oxygen source are introduced into a vacuum reaction furnace tube, and a protective atmosphere is introduced. The temperature is controlled to rise to a specific temperature. After a certain reaction time, a gaseous carbon source and hydrogen as well as a trace amount of oxygen are further introduced. The reaction is carbonized for a certain period of time and cooled to room temperature to obtain a silicon-oxygen-carbon material.

6. The ultra-high specific capacity lithium-ion battery based on silicon oxygen carbon material according to claim 5, characterized in that: The oxygen source gas is one or more of oxygen and carbon dioxide.

7. The ultra-high specific capacity lithium-ion battery based on silicon oxygen carbon material according to claim 5, characterized in that: The specific temperature is 500°C to 2800°C.

8. The ultra-high specific capacity lithium-ion battery based on silicon oxygen carbon material according to claim 5, characterized in that: The reaction time is 10-24 hours.

9. The ultra-high specific capacity lithium-ion battery based on silicon oxygen carbon material according to claim 5, characterized in that: The carbonization time is 10-24 hours.

10. A silicon-oxygen-carbon material, characterized in that: The silicon-oxygen-carbon material in the lithium-ion battery according to any one of claims 1 to 8.